Pengaruh CAR, NPL, dan NIM terhadap Profitabilitas Bank Umum yang Listing di Bursa Efek Indonesia - Wiranti, Wiranti; Yudiantoro, Deny (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The research has a purpose to test and analyze the effect of Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), dan Net Interest Margin (NIM) on the Profitability of banking companies listed on the Indonesian Stock Exchange for the 2015-2021. The population consists of 46 companies banks listed on the IDX. Then, the sample was selected through a purposive sampling technique by specifyng 6 companies banks as research objects. The research method uses panel data regression as measured by the e-views 12 program. The results of the analysis of this study indicate that partially the CAR variable has a positive and significant effect on profitability, meanwhile, the NPL and NIM variables have a negatif and insignificant effect on profitability. The simultaneously, the variables CAR, NPL, and NIM are able to influence Profitability by 45,2% and the remaining 54,8% is influenced by other variables not examined.